Monthly frequency distributions of both dry spells and the number of days with precipitation greater than 25 mm over Peninsular Malaysia - Camerlengo, Alejandro L. (1999)
The study of both the monthly distribution of the number of rain-days greater than 25 mm and the re-evaluation of the dry spell monthly distribution in Peninsular Malaysia is made. It is shown that: (a) the dry spell distribution of the east coast is more regular than both the one in the opposite coast and the one in the central part of the peninsula, (b) different dry spell distributions may be defined at the west coast, (c) a dry spell distribution for the central part of the peninsula is well established, (d) Kuala Lumpur is the area where the largest annual number of rain-days greater than 25 mm is observed, and (e) the monthly number of rain-days greater than 25 mm does not follow its respective monthly (average) distribution of rainfall.